The Effect of Tiktok Social Media Marketing and Fear of Missing Out (FoMO) on Impulsive Buying of Adidas Samba Products Among Generation Z in Garut Regency - Fatih Ulayya; Oktri Mohammad Firdaus; Gita Garliani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2026)
This study aims to analyse the Influence of TikTok Social Media Marketing and Fear of Missing Out (FOMO) on impulsive buying among Generation Z in Garut Regency. The Research method used is a descriptive, verifiable, quantitative method with a sample size of 250 respondents. Data analysis techniques use Partial Least Squares-based Structural Equation Modelling SEM-PLS. The results of the study indicate that TikTok Social Media Marketing and FOMO have a positive and significant effect on impulsive buying, both partially and simultaneously. These findings emphasise the importance of responsible management of digital marketing strategy.